2006
DOI: 10.1002/ange.200602670
|View full text |Cite
|
Sign up to set email alerts
|

Synthese und Struktur eines ultradünnen Alumosilicatfilms

Abstract: Abbildung 2. Aufsichten und Perspektivansichten des {AlO 4 }-und des {AlO 3 }-Modells für Alumosilicatfilme auf Mo(112).Abbildung 3. O1s-Region der PE-Spektren des Siliciumoxid-und des Alumosilicatfilms (Al/Si % 1:5) bei normaler und flacher Emission. Angewandte Chemie 7799

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
4
0
3
Order By: Relevance
“…Modeling such materials under controlled conditions, and taking advantage of the analytical tools commonly used in surface science, would provide a new playground for exploring structures and chemical reactions on zeolites. The preparation of well‐defined aluminosilicate thin films was first reported using a Mo(112) substrate 2. It was shown that this film consists of a single layer network of corner‐sharing [SiO 4/2 ] tetrahedra and [AlO 3/2 ] units, and the film is strongly bound to the Mo(112) surface by Si‐O‐Mo linkages (Figure 1 a).…”
Section: Dft (Pbe+d) Results For Angles [°] Bond Distances [Pm] Andmentioning
confidence: 99%
“…Modeling such materials under controlled conditions, and taking advantage of the analytical tools commonly used in surface science, would provide a new playground for exploring structures and chemical reactions on zeolites. The preparation of well‐defined aluminosilicate thin films was first reported using a Mo(112) substrate 2. It was shown that this film consists of a single layer network of corner‐sharing [SiO 4/2 ] tetrahedra and [AlO 3/2 ] units, and the film is strongly bound to the Mo(112) surface by Si‐O‐Mo linkages (Figure 1 a).…”
Section: Dft (Pbe+d) Results For Angles [°] Bond Distances [Pm] Andmentioning
confidence: 99%
“…Recently, 2D counterparts for 3D porous materials have been developed . One system, already mentioned, is SiO 2 /Mo(112) .…”
Section: Thin Film Functionalization Via Selective Dopingmentioning
confidence: 99%
“…As pore diameters in zeolites and silicates are adjustable between 5-100 Å, size-selective adsorption and reaction schemes can be realized. 4,5 The system consists of an ultra-thin silicon-dioxide film that is prepared on a Mo(112) surface. 6,7,8 The fundamental building blocks of the oxide layer are six-membered -Si-O-rings, enclosing a hole of 3-4 Å diameter.…”
Section: Introductionmentioning
confidence: 99%